Челюсть пещерного льва из русла реки Вишни - Татаринов, К.А. (Вестник зоологии, 1969)
The article deals with brief information on the places within the boundary of the Ukraine where the bone remains of Fells spelaea G о 1 d f u s s, 1823 were found. It is mentioned that hitherto in the western parts of the republic the bones of this beasts were registered only in Zhekhovitsa (Volyn) and Sinyakovo (Podo-lia). In May, 1967, the author found the low left jaw of F spelaca on the right bank of the Vishnya river near the town of Rudki, Sambor district, Lvov region (Forecarpathians). In the tables applied the morphometric indices are shown of low jaws of these animals from the spelaea group, found in the Forecarpathians, Moldavia, East Siberia, Transcaucasia. Considerations are made on paleogeographical conditions of the territory under examination in the Pleistocene — Early Holocene, on ecology of F. spelaea and reasons of their extinction.